Burnout and intentions to quit the practice among community pediatricians: associations with specific professional activities - Zachi Grossman; Gabriel Chodick; Talma Kushnir; Herman Avner Cohen; Gil Chapnick; Shai Ashkenazi (BMC, 2019)
Abstract Background Burnout is an occupational disease expressed by loss of mental and physical energy due to prolonged and unsuccessful coping with stressors at work. A prior survey among Israeli pediatricians published in 2006 found a correlation between burnout and job structure match, defined as the match between engagement with, and satisfaction from, specific professional activities. The aims of the present study were to characterize the current levels of burnout and its correlates among community pediatricians, to identify changes over time since the prior survey, and to identify professional activities that may reduce burnout. Methods A questionnaire was distributed among pediatricians both at a medical conference and by a web-based survey. Results Of the 518 pediatricians approached, 238 (46%) responded to the questionnaire. High burnout levels were identified in 33% (95% CI:27-39%) of the respondents. Higher burnout prevalence was found among pediatricians who were not board-certified, salaried, younger, and working long hours. The greater the discrepancy between the engagement of the pediatrician and the satisfaction felt in the measured professional activities, the greater was the burnout level (p < 0.01). The following activities were especially associated with burnout: administrative work (frequent engagement, disliked duty) and research and teaching (infrequent engagement, satisfying activities). A comparison of the engagement-satisfaction match between 2006 and 2017 showed that the discrepancy had increased significantly in research (p < 0.001), student tutoring (P < 0.001), continuing medical education and participation in professional conferences (P = 0.0074), management (p = 0.043) and community health promotion (P = 0.006). A significant correlation was found between burnout and thoughts of quitting pediatrics or medicine (p < 0.001). Conclusions Healthcare managers should encourage diversification of the pediatrician's job by enabling greater engagement in the identified "anti-burnout" professional activities, such as: participation in professional consultations, management, tutoring students and conducting research.